Exploring cancer survivors' preferences for a physical activity maintenance program - Anderson, Hadalyn, author; Leach, Heather, advisor; Fruhauf, Christine, committee member; Faro, Jamie, committee member (Colorado State University. Libraries, 2023)
Purpose: Physical activity (PA) offers long-term health benefits for cancer survivors (CS), if sustained. Community-based exercise programs have shown short-term effectiveness in increasing PA among cancer survivors, but evidence of their effect on long-term PA engagement (i.e., PA maintenance) is lacking. This study (1) quantitatively explored cancer survivors' preferences for a PA maintenance program and whether preferences were impacted by PA levels, and (2) qualitatively explored participants' preferences of a PA maintenance program and PA-related barriers. Methods: CS who completed one of three original cancer-specific community-based exercise programs participated in a pilot PA maintenance program (i.e., two exercise and discussion sessions). (1) Participants completed questionnaires via REDCap database to assess interest in a PA maintenance program (i.e., likelihood of attending, perceived helpfulness and enjoyment, and preferences of frequency, duration, and time until maintenance program commencement) and PA levels. Participants reported current PA levels compared to when they finished the original program (greater or same vs. lower PA levels) and completed the Godin Leisure-Time Exercise Questionnaire to determine whether they were currently meeting PA guidelines (≥150 mins/week of moderate aerobic PA + 2 days of strength training). (2) Participants also completed semi-structured focus groups via Zoom that aimed to answer the following questions regarding participants': (i) maintenance program experience, (ii) suggestions for future maintenance program implementation, (iii) perceived elements of the original program that were helpful in maintaining PA, and (iv) barriers experienced following the original program. Frequencies from (1) were calculated, and Fisher's exact tests were used to compare proportions between maintenance program preferences and participants' PA levels. Qualitative data from (2) were transcribed verbatim, coded inductively, and analyzed using thematic analysis. Themes and frequencies of references (%) were calculated. Results: (1) Participants (N=20) were M=60±13 years old, non-Hispanic White (95%), female (95%), and diagnosed with breast (50%), ovarian (20%), or other (30%) cancer. Average time since program completion was M=26.2 ± 35.7 (1-110) months. Most participants (65%) reported exercising more or the same amount since original program completion, and 35% met PA guidelines. The majority were likely to attend maintenance exercise (90%) and discussion (80%) sessions. All (100%) participants thought maintenance exercise sessions would be helpful and most (85%) for discussion sessions. There were no differences in responses based on PA levels (all p>.05). (2) Themes identified for (i) were Accountability (36%), Shared Cancer Survivor Experience (26%), Individualized Exercise Prescription (30%), and Discussion Session Content (8%); (ii) were Accountability (8.929%), Discussion Session Content (26.79%), and Discussion (19.64%) and Exercise (44.64%) Session Delivery; (iii) were Accountability (39.39%), Individualized Exercise Prescription (30.3%), and Discussion Session Content (30.3%); and (iv) were Psychological (41.38%), Physical (27.59%), and Environmental (31.03%). Conclusion: Participants had positive perceptions of the maintenance program. Future studies should measure effectiveness of a maintenance program to support PA maintenance and encompass program leader perspectives to work towards achieving pragmatic solutions to maintain PA maintenance programs within community-based settings.